Reseña de: ZAKARIA, Fareed, "El mundo después de USA", Ed. Espasa, Madrid, 2009 - Juan TOVAR (Relaciones Internacionales, 2009)
Reseña de: ZAKARIA, Fareed, "El mundo después de USA", Ed. Espasa, Madrid, 2009.